Mindfulness attenuates both emotional and behavioral reactions following psychological contract breach: A two-stage moderated mediation model - Shaffakat, Samah (Institutional Knowledge at Singapore Management University, 2022)
Breach of the psychological contract between organization and employee often evokes employee hostility, which in turn can instigate deviant behaviors. We examine whether employee mindfulness attenuates these reactions to psychological contract breach. Specifically, we develop and test a two-stage moderated mediation model in which employee mindfulness moderates the mediational path from psychological contract breach via hostility to deviance by attenuating both emotional and behavioral reactions. Findings across four studies (with 872 employee participants) both measuring and manipulating breach and mindfulness demonstrate substantial support for the proposed model. Further analyses including alternative moderators, mediators, and dependent variables provide evidence for discriminatory and incremental validity. We discuss theoretical and practical implications as well as future research avenues.